Validation of the basic need satisfaction for sport scale in Ethiopian athletes - Melesse, Getabirhan Getinet; Tegegne, Zelalem Melkamu; Rani, Sangeeta (Frontiers in Sports and Active Living, 2024)
By anchoring on the self-determination theory in an Ethiopian context, this study tried to establish the basic need satisfaction sport scales (BNSSS) reliability and validity. Despite the scale's usefulness in measuring athletes' psychological need fulfillment during a sporting event, no study has proven the scale's validity in a setting of Ethiopian sports. To validate the BNSSS scale, confirmatory factor analysis was used in the study. The 20 items of the BNSSS questionnaire's English translation are divided into five categories: relatedness, competence, autonomy-perceived locus of internal causality, autonomy-choice, and volition. Senior language experts translated the BNSSS questionnaire into Amharic. The Amharic version of the instrument was used to gather data from 321 athletes, 174 men, and 147 women, with a mean age of 23.34 22.59 and a standard deviation of 5.08 and mean age 5.32; a standard deviation of 2.33 year of experience in their sports from four baseball games. With a Cronbach's alpha value ranging from 0.848 to 0.882 (IPLOC to Volition respectively) across the five subscales and, the results confirm the reliability of the BNSSS for evaluating satisfaction with basic needs and motivation among Ethiopian athletes.” The result demonstrated an acceptable fit with the data (CFI, = 0.958, GFI, = 0.933, RMR, = 0.76, RMSEA, = 0.39) as well as internal consistency. All of the components' Cronbach's alpha values met expectations. The instrument's Amharic translation was thus valid and reliable for determining the extent to which Ethiopian athletes' basic needs were met.